Shallot Growth and Yields Based on Ammonium:Nitrate Ratio on Coastal Sandy Soil - Wiji Safitri; Endang Sulistyaningsih; Benito Heru Purwanto; Stephen Harper (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
Nitrogen was a key component for increasing yield and quality of vegetables like shallots. The growth and development of plants were influenced by nitrogen form. Common plants preferred nitrate for growth, but the enormity preference varies within plant species and other environmental factors. The purpose of this experiment was to study the effect of ammonium:nitrate ratio in sandy soil to growth and yield of shallot (Allium cepa L. Aggregatum group). The experiment had been conducted in August-October 2015 in the sandy land on Samas Beach, Bantul, Yogyakarta, Indonesia. The research was arranged in a Split-Plot design. The main plot was the source of nitrogen (NH4+; NO3-; NH4+: NO3- 1:1; NH4+: NO3- 1:2; and NH4+: NO3- 2:1) and the subplot was cultivars (Crok Kuning, Tiron, and Bima Brebes). Each subplot covered an area of 2.5 m² (2.5 m x 1 m) with three blocks as replications. Shallot bulbs were planted in sixth-row, spacing 20 cm between rows and 15 cm within rows. The dose was applied according to the recommendation of BPTP (urea 200 kg ha-1, ZA 250 kg ha-1, SP-36 150 kg ha-1, and KCl 150 kg ha-1) 144.5 kg N ha-1. Ammonium:nitrate ratio influenced shallot growth in sandy soil through number of leaves at maximum vegetative phase and its leaf area. The NH4+: NO3- 1:2 ratio gave the best result in dry weight of leaves following bulb dry weight than other ratio. Nevertheless, ammonium:nitrate ratio had no significant influence on bulb dry weight (ton ha-1).